Principy a využití kometové analýzy při detekci poškození DNA - Dvořák, Miroslav; Matejovičová, Milena (Chemické listy, 2008)
This review provides a brief information on principles and possible applications of the comet assay method, known as single cell gel electrophoresis, allowing to analyze DNA damage. This method developed in the mid-seventies was widely used in the early eighties of the last century. Several modifications of the comet assay approach made this method an attractive tool in various fields such as molecular biology research, quality control, clinical diagnosis, and monitoring of environmental pollution.
Keywords: mutageneze; financování organizované; kometový test; Financing, Organized; DNA Damage; apoptóza; poškození DNA; Comet Assay; Apoptosis; Mutagenesis